Design of novel multifunctional targeting nano-carrier drug delivery system based on CD44 receptor and tumor microenvironment pH condition. (23rd March 2016) - Chen, Daquan; Lian, Shengnan; Sun, Jingfang; Liu, Zongliang; Zhao, Feng; Jiang, Yongtao; Gao, Mingming; Sun, Kaoxiang; Liu, Wanhui; Fu, Fenghua
Abstract: In this study, to develop a multifunctional targeting nano-carrier drug delivery system for cancer therapy, the novel pH-sensitive ketal based oligosaccharides of hyaluronan (oHA) conjugates were synthesized by chemical conjugation of hydrophobic menthone 1, 2-glycerol ketal (MGK) to the backbone of oHA with the histidine as the linker of proton sponge effect. The multifunctional oHA conjugates, oHA-histidine-MGK (oHM) carried the pH-sensitive MGK as hydrophobic moieties and oHA as the target of CD44 receptor. The oHM could self-assemble to nano-sized spherical shape with the average diameters of 128.6 nm at pH 7.4 PBS conditions. The oHM nanoparticles (oHMN) could release encapsulated curcumin (Cur) with 82.6% at pH 5.0 compared with 49.3% at pH 7.4. The results of cytotoxicity assay indicated that encapsulated Cur in oHMN (Cur-oHMN) were stable and have less toxicity compared to Cur suspension. The anti-tumor efficacy in vivo suggested that Cur-oHMN suppressed tumor growth most efficiently. These results present the promising potential of oHMN as a stable and effective nano-sized pH-sensitive drug delivery system for cancer treatment.